Arabic Language Learning Strategy Based on Pesantren Local Wisdom: An Effort to Maintain Cultural Identity - Hindun , Hindun; Humaidi , Humaidi; Bakr , Mohamed Abu (Al-Insyiroh: Jurnal Studi Keislaman, 2024)
This study aims to reveal how integrating local wisdom in Arabic language learning strategis can be an effective effort in maintaining the cultural identity of the people who use the language. Cultural identity is often closely related to language, and in the context of Arabic language teaching, efforts to maintain cultural identity can be challenging. This research uses a qualitative approach by analyzing related literature, case studies, field observations and interviews. The results of this study show that integrating local wisdom in the Arabic learning strategi can help students to be more effective in understanding the rules of Arabic and reading the kutub turats. This is done by combining Arabic learning methods with pesantren local wisdom such as singing lalaran nadham accompanied by rabana, takror ziarah, interpreting the kutub turats with the style of pesantren and understanding the kutub turats with the pesantren bahtusl masa'il nahwiyah. In addition, this study also shows that learning Arabic as a means to spread and understand the local wisdom of pesantren is also a strong tool in strengthening cultural identity, especially pesantren culture. It can also help address issues related to globalization and cultural homogenization. The results of this study are expected to provide guidance for the development of an Arabic language learning strategi that is more oriented towards the local wisdom of pesantren, so that it can help the community to maintain and appreciate the cultural identity of pesantren in this digital era.